2018
DOI: 10.5114/wiitm.2018.77276
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory complications following mini-invasive laparoscopic and thoracoscopic esophagectomy for esophageal cancer. Experience in 215 patients.

Abstract: IntroductionRespiratory complications (RC) including respiratory failure and adult respiratory distress syndrome (ARDS) affect the outcomes of esophagectomy substantially. In order to decrease their incidence, identification of important features of RC is necessary.AimTo evaluate the incidence and risk factors of postoperative RC following hybrid esophagectomy.Material and methodsThe retrospective analysis of consecutive hybrid esophagectomies for malignancies (transhiatal laparoscopic or thoracoscopic resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
2
1
Order By: Relevance
“…The results revealed that the incidence of overall complications was 45.2% and the incidence of respiratory complications was 28.3% in the control group. The respiratory complication was lower than that reported by a previous study (40% respiratory complication) [ 21 ]. Furthermore, patients in the control group had a lower incidence of postoperative anastomotic leakage, when compared to the incidence reported by a previous study [ 22 ].…”
Section: Discussioncontrasting
confidence: 70%
“…The results revealed that the incidence of overall complications was 45.2% and the incidence of respiratory complications was 28.3% in the control group. The respiratory complication was lower than that reported by a previous study (40% respiratory complication) [ 21 ]. Furthermore, patients in the control group had a lower incidence of postoperative anastomotic leakage, when compared to the incidence reported by a previous study [ 22 ].…”
Section: Discussioncontrasting
confidence: 70%
“…Patients with locally advanced ESCC have a poor prognosis. Previous studies [1,4,39] have reported that a high rate of postoperative complications, especially pulmonary complications, is one of the reasons that lead to poor a prognosis. In our study, we found that patients with postoperative pulmonary complications had worse OS and DFS, which further supports previous ndings.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive techniques have been preferred over the past decade. Less surgical trauma, fewer respiratory complications, and shorter recovery period are reported in cases of minimally invasive oesophagectomy [ 5 , 6 ]. Hybrid oesophagectomy is also associated with better postoperative outcomes compared to the open approach, especially concerning pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%